2009
DOI: 10.1007/s10877-009-9197-5
|View full text |Cite
|
Sign up to set email alerts
|

BIS values during resuscitation: the role of the suppression ratio (case report)

Abstract: We report a case during which it was simultaneously recorded usual Bispectral Index (BIS) values and elevated suppression ratio (SR) during resuscitation maneuvers. A 52-year-old woman, scheduled for a suspension laryngoscopy, required cardio-pulmonary resuscitation due to an anaphylactic shock secondary to the administration of succinylcholine. Post-crisis analysis of the BIS trace showed both BIS numbers consistent with an adequate level hypnosis and an increase in SR. Simultaneous hypnotic BIS values and an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…A BSP not only appears under the effect of anesthetics; it has also been reported in comatose patients after traumatic brain injury, hypoglycemic coma, hypoxemia, vascular brain injury, cases of overdose of drugs that depress central nervous system activity, profound hypothermia, anoxic-ischemic encephalopathy after cardio-respiratory arrest, patients with any severe diffuse encephalopathy, and during any stage of neonatal sleep (De Rubeis & Young, 2001; Declerck, Liu, Chazot, & Fischler, 2009; Hayashida et al, 2007; Johansen, 2001; Levy, Pantin, Mehta, & McGarvey, 2003; N. Liu, Chazot, Mutter, & Fischler, 2006; Marion et al, 1997; Michenfelder & Milde, 1991; Myles & Cairo, 2004; Nakashima, Todd, & Warner, 1995; Ernst Niedermeyer & Lopes Da Silva, 2005; E.…”
Section: Bsp Not Related To Anesthesiamentioning
confidence: 99%
“…A BSP not only appears under the effect of anesthetics; it has also been reported in comatose patients after traumatic brain injury, hypoglycemic coma, hypoxemia, vascular brain injury, cases of overdose of drugs that depress central nervous system activity, profound hypothermia, anoxic-ischemic encephalopathy after cardio-respiratory arrest, patients with any severe diffuse encephalopathy, and during any stage of neonatal sleep (De Rubeis & Young, 2001; Declerck, Liu, Chazot, & Fischler, 2009; Hayashida et al, 2007; Johansen, 2001; Levy, Pantin, Mehta, & McGarvey, 2003; N. Liu, Chazot, Mutter, & Fischler, 2006; Marion et al, 1997; Michenfelder & Milde, 1991; Myles & Cairo, 2004; Nakashima, Todd, & Warner, 1995; Ernst Niedermeyer & Lopes Da Silva, 2005; E.…”
Section: Bsp Not Related To Anesthesiamentioning
confidence: 99%
“…Also, the burst suppression ratio, derived from BIS monitoring, is correlated with the burst suppression and could be an indicator of anesthesia that is too deep [14]. Several reports have suggested that the burst suppression ratio is associated with intraoperative metabolic disorders or brain injury [15,16,17], and postoperative prognosis and delirium [18,19,20].…”
Section: Introductionmentioning
confidence: 99%